Household sanitation facilities and women's risk of non-partner sexual violence in India. (December 2016) - Jadhav, Apoorva; Weitzman, Abigail; Smith-Greenaway, Emily
Abstract Background Globally, one in ten individuals practice open defecation. Despite media speculation that it increases women's risk of sexual violence, little empirical evidence supports the claims. We investigate the relationship between household sanitation facilities and women's risk of non-partner sexual violence (NPSV) in India, where nearly half of the population lives without a pit or toilet. Methods We use the most recent NPSV data, from the National Family Health Survey-III, to estimate logistic regression models of the effects of household sanitation facilities (toilet, pit, or none) on NPSV in the last year among women who have resided in their current home for one year or more. These effects are estimated net of other socioeconomic factors, compared to effects of household sanitation facilities on child diarrhea, and, as a falsification test, compared to effects of household sanitation facilities on intimate partner sexual violence (IPSV) in the last year. Results Net of their socioeconomic status, women who use open defecation are twice as likely to face NPSV as women with a household toilet. This is twice the association between open defecation and child diarrhea. The results of our falsification test indicate that open defecation is not correlated with IPSV, thus disconfirming a simultaneous selection of women into open defecation and sexual violence. Conclusions Our findings provide empirical evidence that lacking household sanitation is associated with higher risk of NPSV.